Producción arrocera y su incidencia en los pequeños productores en el recinto Guachapeli del cantón Samborondón en la provincia del Guayas - Montenegro Zúñiga, Elvis Patricio (2018)
The "Guachapelí" enclosure belonging to the Canton Samborondón, is a rice area par excellence, where the majority of its inhabitants are dedicated to the cultivation or rice crops as their main economic income, however, it has been possible to demonstrate that the rice producers of the area has internal and external factors that affect its production, such as the attack of different pests, the lack of capital to cover the maintenance of the various processes and improve their production, the flood-vulnerable zone, the smuggling of rice from Peru and the price of the rice sack; for this reason the general objective of this work is to analyze the current conditions of rice production obtained in the Guachapelí enclosure located in the Canton Samborondón belonging to the province of Guayas, and the socio-economic impact they have on the farmers of the grass, thus having the possibility of developing aspects of technical-economic advice that help improve rice production of small farmers in the canton. The type of research used for the respective study is exploratory, descriptive and explanatory, and the approach is mixed, that is, qualitative and quantitative……….